Orthotopic tumorgrafts in nude mice: A new method to study human prostate cancer. Issue 14 (12th June 2015) - Saar, Matthias; Körbel, Christina; Linxweiler, Johannes; Jung, Volker; Kamradt, Jörn; Hasenfus, Andrea; Stöckle, Michael; Unteregger, Gerhard; Menger, Michael D.
<x xml:space="preserve">Abstract</x> BACKGROUND In vivo model systems in prostate cancer research that authentically reproduce tumor growth are still sparse. While orthotopic implantation is technically difficult, particularly in the mouse, most models favor subcutaneous tumor growth. This however provides little information about natural tumor growth behavior and tumor stroma interaction. Furthermore, established prostate cancer cell lines grown as in vivo xenografts are not able to reflect the variety of tumor specific growth patterns and growth behavior in men. Primary cell cultures are difficult to handle and an induction of orthotopic tumors has not been successful yet. Therefore, a tumorgraft model using tumor tissue from prostatectomy specimens was developed. METHODS Balb/c nude mice were used to graft fresh prostate tumor tissue by renal subcapsular and orthotopic implantation. Testosterone propionate was supplemented. Animals were tracked by means of 30 MHz ultrasound to monitor tumor engraftment and growth. Autopsy, histology, PSA measurements as well as immunostaining and PCR for human tissue were performed to confirm orthotopic tumor growth. RESULTS Renal subcapsular engraftment was seen in 2 of 3 mice. Orthotopic engraftment was observed in 7 of 11 animals (63.6%) with an overall engraftment of 5 out of 9 patient specimens (55.6%). Ultrasound confirmed the tumor growth over time. Of interest, the tumorgrafts not only retained essential features of the parental tumors, but also stained positive for tumor specific markers such as AR, PSA, and AMACR. Tumor positive animals showed highly elevated serum PSA levels with confirmation of a human specific PCR sequence and a human endothelial cell lining in the tumor vessels. CONCLUSIONS Standardized implantation of fresh tumor tissue in nude mice prostates generates tumorgrafts with histological properties of organ‐confined prostate cancer. These tumorgrafts display a new approach for an optimized in vivo model of prostate cancer and will allow further investigations on specific pathways of tumor initiation and progression as well as therapeutic response. Prostate 75:1526–1537, 2015. © 2015 Wiley Periodicals, Inc.